2015
DOI: 10.1371/journal.pone.0128681
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cataract on Early Stage Glaucoma Detection Using Spatial and Temporal Contrast Sensitivity Tests

Abstract: BackgroundTo investigate the effect of cataract on the ability of spatial and temporal contrast sensitivity tests used to detect early glaucoma.MethodsTwenty-seven glaucoma subjects with early cataract (mean age 60 ±10.2 years) which constituted the test group were recruited together with twenty-seven controls (cataract only) matched for age and cataract type from a primary eye care setting. Contrast sensitivity to flickering gratings at 20 Hz and stationary gratings with and without glare, were measured for 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
0
6
0
1
Order By: Relevance
“…Notably, in 2016 there were 3450 distraction-related deaths, which included the use of mobile telephones. 28 Despite restrictions on the use of mobile telephones while driving in many states, it seems not to be a rare habit. When asked about driving habits and mobile telephone use while driving, patients with glaucoma gave responses that were similar, on average, with controls’.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in 2016 there were 3450 distraction-related deaths, which included the use of mobile telephones. 28 Despite restrictions on the use of mobile telephones while driving in many states, it seems not to be a rare habit. When asked about driving habits and mobile telephone use while driving, patients with glaucoma gave responses that were similar, on average, with controls’.…”
Section: Discussionmentioning
confidence: 99%
“…Glaucomatous damage has been found to be moderately positively correlated with increased glare factor (rho = 0.485; P = 0.01), with glare factor being the difference between log CS with glare and log CS without glare. 37 It should be noted, however, that this finding comes from a study in which all participants had cataract. log unit luminance change).…”
Section: Glarementioning
confidence: 87%
“…Grating CS tests are promising for the detection of early glaucoma and its progression (32,34) . Klein et al (17) suggested that spatial CS were a sensitive indicator of early glaucomatous loss in the presence of cataracts. Although visual acuity was good, the CS of the eyes with glaucoma was significantly less than among healthy subjects except at 1.5 cpd (p<0.012).…”
Section: Discussionmentioning
confidence: 99%
“…CS decreases in all stages of glaucoma and age-related macular degeneration (AMD) have been documented using different testing methods (7,(12)(13)(14)(15) . Glaucoma, cataract, and AMD patients suffer from pro blems in vision-related activities of daily living and the inability to recognize targets in real world, which can be better identified by CS tests than by visual acuity tests (14,(16)(17)(18) . The increasing importance of visual quality and the need for accurate measurement of visual acuity has led to more interest in CS tests (12,(19)(20)(21) .…”
Section: Introductionmentioning
confidence: 99%